Intravenous ketamine for adult procedural sedation in the emergency department: a prospective cohort study. Issue 8 (25th July 2008) - Newton, A; Fitton, L
Abstract : Objectives: To evaluate the use of intravenous ketamine for procedural sedation in adults attending the emergency department. Methods: A prospective study was performed over a 2-year period in 92 patients who received intravenous ketamine for procedural sedation in the emergency department of St Thomas' Hospital. All patients received 0.5–1.0 mg/kg ketamine intravenously for the procedure. Pulse rate, blood pressure oxygen saturations and incidence of adverse events (clonic movements, hypersalivation, laryngospasm, recovery agitation and vomiting) were recorded for all patients. Results: Adequate sedation was obtained in 91 of the 92 patients (98.9%) and successful completion of the procedure was achieved in 91 patients (98.9%). Adverse events occurred in 20 patients (21.7%). Four patients (7%) developed clonic movements, none of which required treatment. Twelve patients (13.0%) developed recovery agitation. In five cases the agitation was transient and required no treatment; the other seven patients were treated with intravenous midazolam. One of the patients who experienced recovery agitation also developed vomiting. Two other patients vomited, and one patient had vomiting and hypersalivation. One further patient developed hypersalivation. There were no reported episodes of laryngospasm. Conclusions: Ketamine is an effective agent for procedural sedation in the emergency department. There were no serious adverse events associated with its use, but there is a significant incidence of recovery agitation which may require treatment with a benzodiazepine.